2021
DOI: 10.1007/s10654-021-00722-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality in the UK Biobank cohort: revisiting and evaluating risk factors

Abstract: Most studies of severe/fatal COVID-19 risk have used routine/hospitalisation data without detailed pre-morbid characterisation. Using the community-based UK Biobank cohort, we investigate risk factors for COVID-19 mortality in comparison with non-COVID-19 mortality. We investigated demographic, social (education, income, housing, employment), lifestyle (smoking, drinking, body mass index), biological (lipids, cystatin C, vitamin D), medical (comorbidities, medications) and environmental (air pollution) data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 43 publications
9
101
0
3
Order By: Relevance
“…27 Our findings of an association of persistent symptoms with deprivation, and with smoking or vaping, are not well described in the literature, although smokers have been found to have a higher risk of severe COVID-19. 28 Our identification of two stable and well-differentiated symptom clusters at 12 weeks supports the characterisation of Long COVID as a diverse set of overlapping conditions.…”
Section: Discussionsupporting
confidence: 73%
“…27 Our findings of an association of persistent symptoms with deprivation, and with smoking or vaping, are not well described in the literature, although smokers have been found to have a higher risk of severe COVID-19. 28 Our identification of two stable and well-differentiated symptom clusters at 12 weeks supports the characterisation of Long COVID as a diverse set of overlapping conditions.…”
Section: Discussionsupporting
confidence: 73%
“…In line with previous (i.e., early and recent) analysis of COVID-19 risk [7,8,16,17], we found that age and underlying conditions such as diabetes, arterial hypertension, and cardiovascular diseases signi cantly contributed to the risk of severe disease outcomes, particularly hospital admission. However, rather than individual diagnoses, the comorbidity burden was a stronger predictor of hospital admissions and deaths.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that individual-level and neighborhood-level variables provide complementary information about the contribution of socioeconomic conditions to health outcomes, 65 and both will be available to be tested as potentially significant factors associated with COVID-19 outcomes in our sample. The use of such variables should allow us to investigate the extent to which the vulnerability to more severe COVID-19 might be predicted not only by age, ethnicity and medical factors (eg, number of comorbidities) 71 but also socially determined factors such as poor housing conditions, unstable income and delayed access to health services. 72 Once our analyses will be carried out in a large urban LMIC setting, unique information may be gathered regarding the influence of disadvantaged socioeconomic status on specific long-term COVID-19 manifestations.…”
Section: Discussionmentioning
confidence: 99%